Use of a postoperative pad test to identify continence status in women after obstetric vesicovaginal fistula repair: a prospective cohort study. (27th January 2017) - Kopp, DM; Bengtson, AM; Tang, JH; Chipungu, E; Moyo, M; Wilkinson, J
Abstract : Objective: Determine whether a 1‐hour pad test at discharge can identify continence status within 120 days of obstetric vesicovaginal fistula (VVF) repair. Design: Prospective cohort study. Setting: Fistula Care Centre in Lilongwe, Malawi. Population: Women with VVF who underwent repair between January 2012 and December 2014. Methods: Data on demographics, obstetric history, physical exam findings, operative management, postoperative findings, and follow up evaluations were collected on women with VVF repair. Main outcome measures: Sensitivity, specificity, positive and negative predictive values (PPV and NPV), and a receiver operating curve (ROC) were calculated to assess the utility of using a discharge pad test at three thresholds to identify women likely to be continent at follow up. Results: After VVF repair, 346 women had a 1‐hour pad test performed at the time of hospital discharge and completed follow up within 120 days of repair. Of these, 79.8% ( n  = 276) were completely continent, whereas 20.2% ( n  = 70) had some degree of incontinence. The sensitivity and specificity of a negative 1‐hour pad test at predicting continence is 68.1% and 82.9%, respectively. With this prevalence, a negative pad test at a 1.5‐g threshold demonstrates a high predictive value (PPV = 94.0%, 95% CI 90.0–96.9) in detecting women with continence after repair. Conclusions: At the 1.5‐g threshold, a negative pad test at discharge identifies 94% of women who will remain continent after VVF repair. Adding the pad test to fistula care can identify women who are likely to remain continent and may not need further therapies in settings where resources are limited and follow up after repair is difficult. Tweetable abstract: A negative pad test after repair is associated with continued continence at follow up. Tweetable abstract: A negative pad test after repair is associated with continued continence at follow up.